2021
DOI: 10.1158/1078-0432.ccr-21-1546
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Mesothelin with Chimeric Antigen Receptor T Cells in Acute Myeloid Leukemia

Abstract: has equity ownership in Hematologics, Inc. S.F. holds provisional patents filed on the use of CAR-T cell therapy for hematologic malignancies and is a medical and scientific advisor for Link Immunotherapeutics. C.J.T receives research funding from Juno Therapeutics/BMS, Nektar Therapeutics, Minerva, AstraZeneca, TCR 2 Therapeutics; is a member of scientific advisory boards for Precision Biosciences, Eureka Therapeutics, Caribou Biosciences, T-CURX, Myeloid Therapeutics, ArsenalBio, and Century Therapeutics; ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Among the 7 reported R/R AML patients, the CR/CRi rate was 42% (157). Moreover, CAR-T cells redirected to several novel targets [FLT3 (158,159), CLL-1 (160), CD70 (161), IL-10R (162), mesothelin (163), Siglec-6 (164), etc.] have shown potent efficacy in preclinical studies, and some of them (eg., CLL-1) are currently being assessed in clinical trials (150).…”
Section: Car-t and Car-nk Cellsmentioning
confidence: 99%
“…Among the 7 reported R/R AML patients, the CR/CRi rate was 42% (157). Moreover, CAR-T cells redirected to several novel targets [FLT3 (158,159), CLL-1 (160), CD70 (161), IL-10R (162), mesothelin (163), Siglec-6 (164), etc.] have shown potent efficacy in preclinical studies, and some of them (eg., CLL-1) are currently being assessed in clinical trials (150).…”
Section: Car-t and Car-nk Cellsmentioning
confidence: 99%
“…Multiple additional antigens have been tested preclinically or in a clinical setting in the quest for better CAR-T cell target proteins. Apart from those described above, the following antigens have either been examined for AML or are being investigated: CD7, CD13, CD19, CD34, CD38, CD56, CD117, B7-H3, mesothelin, NKG2D ligands, IL-10 receptor, GM-CSF receptor, ILT3, TIM-3, MUC-1, Lewis Y, and folate receptor β [ 46 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ] ( Table 1 ).…”
Section: Aml Target Antigens Under Investigationmentioning
confidence: 99%
“…Similar MSLN expression patterns (MFI, 70.4 ± 24.0%) were also seen in bulk AML cells from MSLN-positive patients, while MSLN expression was entirely absent in normal hematopoietic cells. 31 These results…”
Section: Msln and Secondary Diseases Of Amlmentioning
confidence: 71%
“…Recent research has shown that MSLN is highly expressed in LSCs. 31 The CD34 + CD38fraction of LSCs from 5 MSLNpositive patients was MSLN + (MFI, 67.1 ± 26.6%) by flow cytometry.…”
Section: Msln and Secondary Diseases Of Amlmentioning
confidence: 90%